Ceratopteris shingii, a new species of Ceratopteris with creeping rhizomes from Hainan, China - Zhang, Rui; Yu, Jun-Hao; Shao, Wen; Wang, Wei-Qing; Shang, Hui; Zheng, Xi-Long; Yan, Yue-Hong (Phytotaxa, 2020)
A new species of fern, Ceratopteris shingii (Pteridaceae), was identified and characterized. It is endemic to Hainan Province, China. Ceratopteris shingii shares similar morphological characters with C. thalictroides but can be easily distinguished by its creeping rhizomes. In addition, molecular evidence indicated that the new species is sister to other Ceratopteris species.